2022
DOI: 10.1101/2022.10.04.509789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital nanoreactors for control over absolute stoichiometry and spatiotemporal behavior of receptors within lipid bilayers

Abstract: Interactions between membrane proteins are essential for cell survival and proper function, but the structural and mechanistic details of these interactions are often poorly understood. Even the biologically functional ratio of protein components within a multi-subunit membrane complex—the native stoichiometry—is difficult to establish. We have demonstrated digital nanoreactors that can control interactions between lipid-bound molecular receptors along three key dimensions: stoichiometric, spatial, and tempora… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…274 In addition to providing control over lipid architectures, lipid vesicle-templating DNA origami has also been applied to precisely position molecules onto membranes and study reaction kinetics with absolute control over stoichiometry. 275…”
Section: Dna Nanotechnologymentioning
confidence: 99%
“…274 In addition to providing control over lipid architectures, lipid vesicle-templating DNA origami has also been applied to precisely position molecules onto membranes and study reaction kinetics with absolute control over stoichiometry. 275…”
Section: Dna Nanotechnologymentioning
confidence: 99%
“…Because synthetic small unilamellar vesicles (SUVs) and supported lipid bilayers (SLBs) make the structural and chemical control of model membranes much simpler, they are often used as model systems of cell membranes to study fundamental biophysical processes. 12,13 Many recent studies have reported interactions between GOFNs and SLBs. Li et al suggested that the attachment of GO to membranes was promoted by hydrogen bonding by using SLBs.…”
Section: Introductionmentioning
confidence: 99%
“…54,58 Furthermore, the precisely assembled liposome in the chamber of three-dimensional DNA origami has been creatively developed to mimic the function of the cell membrane for the intelligent detection of membrane protein interactions. 59 Taking advantage of the efficient lipid growth capability on the surface of DNA origami, there is an appealing possibility of creating both lipid-coated and genetically encoded DNA origami for gene delivery. Compared with the commercial liposome, the density of lipids on the coated DNA origami can be easily optimized to find the balance between excellent gene delivery efficiency and negligible cytotoxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, at high dosages, the noticeable cytotoxicity of lipids restricts their wide applications in clinics . Fortunately, due to the excellent addressability, DNA origami with precisely organized anchoring sites can be rationally designed as the template for lipid growth. Based on this DNA origami-templated lipid growth strategy, the size-controlled liposome can be efficiently fabricated. , Furthermore, the precisely assembled liposome in the chamber of three-dimensional DNA origami has been creatively developed to mimic the function of the cell membrane for the intelligent detection of membrane protein interactions . Taking advantage of the efficient lipid growth capability on the surface of DNA origami, there is an appealing possibility of creating both lipid-coated and genetically encoded DNA origami for gene delivery.…”
Section: Introductionmentioning
confidence: 99%